All Together Now : American Holiday Symbolism Among Children and Adults - Clark, Cindy Dell (Book collections on Project MUSE., 2019)
"In All Together Now, Cindy Dell Clark, through a study spanning from 1985 to 2015, addresses major American family holidays, including Easter, Memorial Day, Independence Day, Halloween, Christmas, and Hanukkah and explores the complex interactions within families. Her book integrates children's involvement in American family holidays and is relevant to the broad attempt in the anthropology and sociology of childhood to include children's perspectives in larger theorizing by mainstream disciplines"--